1992
DOI: 10.1288/00005537-199212000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteatoma in the pediatric population: Prognostic indicators for surgical decision making

Abstract: A review of surgical therapy for pediatric cholesteatoma at the Arkansas Children's Hospital was performed. Fifty-three children treated surgically for cholesteatoma were studied over a 10-year period. Primary acquired, or attic retraction cholesteatomas, were generally treated with a canal up tympanomastoidectomy; there were very few complications or secondary procedures in this group. Middle ear or secondary acquired cholesteatomas were initially treated by both canal up and canal down procedures; however, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 7 publications
2
19
0
2
Order By: Relevance
“…10 Factors such as surgeon experience, high facial ridge, inadequate meatoplasty, ossicular chain involvement and cholesteatoma extent have been reported to correlate highly with disease recurrence. 8,[11][12][13][14] In our study, eight of 25 ears demonstrated spontaneous improvement in air conduction thresholds 12 to 18 months following primary surgery. On reexploration, all eight cases had recurrent disease.…”
Section: Discussionmentioning
confidence: 87%
“…10 Factors such as surgeon experience, high facial ridge, inadequate meatoplasty, ossicular chain involvement and cholesteatoma extent have been reported to correlate highly with disease recurrence. 8,[11][12][13][14] In our study, eight of 25 ears demonstrated spontaneous improvement in air conduction thresholds 12 to 18 months following primary surgery. On reexploration, all eight cases had recurrent disease.…”
Section: Discussionmentioning
confidence: 87%
“…Pediatric CC tends to be more aggressive and extensive than CC in adults, and it is associated with a higher rate of recurrence [1011]. According to the report of Potsic, et al [12] the recurrence rate after surgery was 13% among patients with stage I CC and 25% among those with stage II CC, while Stapleton, et al [13] reported that 5% of patients with stage I CC and 24% with stage II CC had recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports [9,10,[19][20][21][22] indicate that operator experience, patient age, ossicular chain involvement, cholesteatoma size and location, and disease left behind at time of surgery correlate with recurrent disease. Most authors agree that recurrence is much more commonly seen when disease involves the round window, sinus tympani and ossicular chain in the posterior-superior quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…We agree with this conclusion and found the majority of our recurrences for both types of approaches were in the posterior/superior quadrant (Chart 3). Stern and Fazekas-May [21] demonstrated that the presence of disease in the sinus tympani necessitates a CWD procedure in 86-92% of patients. However, others argue that sinus tympani disease can still be explored with an ICW via a retrofacial approach with the aid of an endoscope for examination of the deep recess [2].…”
Section: Discussionmentioning
confidence: 99%